The Use of Models to Help Our Understanding of Vision. - Shayler, Geoff (Optometry & Visual Performance, 2015)
In the mid-20th century, Dr A.M. Skeffington developed his four circle concept of vision. Present knowledge of brain neurology permits a greater understanding of the complex visual process. This presentation utilises this knowledge to expand on the Skeffington concept and draws on both school- and practice-based studies to provide a practical evidence base indicating the integration of visual performance with both cortical brain function and educational performance.